Use of nonlinear asymmetrical shock absorber to improve comfort on passenger vehicles - Silveira, M. [UNESP]; Pontes, B. R. [UNESP]; Balthazar, J. M. [UNESP] (Elsevier B.V., 2014)
In this study the behaviour of two different types of shock absorbers, symmetrical (linear) and asymmetrical (nonlinear) is compared for use on passenger vehicles. The analyses use different standard road inputs and include variation of the severity parameter, the asymmetry ratio and the velocity of the vehicle. Performance indices and acceleration values are used to assess the efficacy of the asymmetrical systems. The comparisons show that the asymmetrical system, with nonlinear characteristics, tends to have a smoother and more progressive performance, both for vertical and angular movements. The half-car front asymmetrical system was introduced, and the simulation results show that the use of the asymmetrical system only at the front of the vehicle can further diminish the angular oscillations. As lower levels of acceleration are essential for improved ride comfort, the use of asymmetrical systems for vibrations and impact absorption can be a more advantageous choice for passenger vehicles. (C) 2013 Elsevier Ltd. All rights reserved.